(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Department of Obstetrics and Gynecology Tashkent Medical Academy Annotation Achieving favorable gestational and perinatal outcomes in women with adenomyosis is extremely important. The purpose of the study was to determine the pathogenetic role of adenomyosis in the development of obstetric and perinatal complications to improve the method of treating pathology with pre-conception preparation and to develop a prediction method complication during gestation.